SARS-CoV-2: From the pathogenesis to potential anti-viral treatments - Zarandi, Peyman Kheirandish (Biomed Pharmacother, 2021)
INTRODUCTION: The world is witnessing the spread of one of the members of Coronaviruses (CoVs) family, called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in the 21st century. Considering the short time spent after its prevalence, limited information is known about the effect of the virus mechanism on different organs of the body; meanwhile the lack of specific treatment and vaccine for this virus has exposed millions of people to a big challenge. AREAS COVERED: The review article aims to describe the general and particular characteristics of CoVs, their classification, genome structure, host cell infection, cytokine storm, anti-viral treatments, and inhibition of COVID-19-related ER-mitochondrial stress. In addition, it refers to drugs such as Chloroquine/Hydroxychloroquine, Lopinavir/Ritonavir, darunavir, ribavirin, remdesivir, and favipiravir, which have undergone clinical trials for coronavirus disease 2019 (COVID-19) treatment. This analysis was derived from an extensive scientific literature search including Pubmed, ScienceDirect, and Google Scholar performed. EXPERT OPINION: The effectiveness rate and complications of these drugs can reveal new insights into the potential therapeutic goals for the disease. Moreover, lifestyle change can effectively prevent SARS-CoV-2 infection.